2008
DOI: 10.1111/j.1467-8535.2007.00753.x
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of electronic and paper‐based assignment submission and feedback

Abstract: This paper presents the results of a study evaluating student perceptions of online assignment submission. 47 students submitted assignments and received feedback via features within the Virtual Learning Environment Blackboard™. The students then completed questionnaires comparing their experience of online submission and feedback with traditional methods.Results indicated that 88% of students reported a time saving and many reported financial benefits using online submission. 93% of students preferred having … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 4 publications
2
34
0
Order By: Relevance
“…Moderation ensures "that the examiners or markers are making similar judgments about the learners' performance" [37:2]. The moderation task involves a process of ensuring that assessors used comparable assessment standards by reviewing a sample of learners' work that has been marked [2,3]. Manual moderation "will normally be paper-based.…”
Section: A Manual Moderation and Electronic Moderationmentioning
confidence: 99%
“…Moderation ensures "that the examiners or markers are making similar judgments about the learners' performance" [37:2]. The moderation task involves a process of ensuring that assessors used comparable assessment standards by reviewing a sample of learners' work that has been marked [2,3]. Manual moderation "will normally be paper-based.…”
Section: A Manual Moderation and Electronic Moderationmentioning
confidence: 99%
“…Dalgarno et al [6] found that students supported the widespread use of online feedback, with a majority of students preferring to both submit assignments and view feedback online. Similarly, Bridge and Appleyard [4] observed that students found submitting assignments online to be faster and easier, and more than half of students preferred online feedback. Heaney and Daly [8] also report that students found electronic systems to be easy to use, and the introduction of an online feedback mechanism correlated with higher exam scores.…”
Section: Related Workmentioning
confidence: 99%
“…Heaney and Daly [8] similarly report that course staff preferred leave feedback online, and in particular, staff liked the ability to attach comments inline with source code. Finally, Bridge and Appleyard [4] observe that the turnaround time for online feedback was shorter than that for traditional mechanisms.…”
Section: Related Workmentioning
confidence: 99%
“…Despite the limited evidence base, it is fair to say that educational institutions have eagerly embraced the efficiency gains 45 and pedagogical power of digital communication technology. Modern radiotherapy students enjoy access to rich virtual learning environments providing them with immediate access to resources, assessment and feedback mechanisms, mobile learning facilitation and a raft of communication options.…”
Section: Technology-enhanced Learningmentioning
confidence: 99%